Detection of Microbial Contamination in Some Types of Processed Cheeses available In Local Market. - Mohammed, Sudad J. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Cheese has an outstanding nutritional quality, but is also an efficient vehicle for transmission of diseases to humans and is an excellent medium for bacterial growth and an important source of bacterial infection. when consumed all without pasteurization Salmonella spp. are one of the most frequently reported causes of bacterial foodborne worldwide. Objective: This study was carried out to study the microbiological contamination of processed cheese. Material and Methods: A total of 13 samples of processed cheese were randomly collected from supermarkets in Baghdad, IRAQ. Elven grams of cheese were added to 99ml of sterile diluted peptone water in a flask and shaken well to make 10-¹ dilution .Further dilution were made. 0.1 ml was used to incubate culturemedia (selective) incubated at 37C°and 42C° for 24 hours. Colonies were counted. Bactrac 4300 was used to confirm diagnosis of Salmonella spp. Result: Although none of tested samples contained Salmonella spp. Or Staphylococcus aureus or Escherichia coli either other bacteria using conventional method, one sample of them been contaminated by Salmonella spp. using Bactrac 4300 system. Conclusion: It can be concluded that processed cheese contaminated by this pathogen in this area as well in other countries and might constitute a risk for contamination and Bactrac 4300 a new method used for confirmation.